1997
DOI: 10.1002/mrm.1910370110
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of water extraction fractions in rat brain using magnetic resonance measurement of perfusion with arterial spin labeling

Abstract: The model used for calculating perfusion by MRI techniques that use endogenous water as a tracer assumes that arterial water is a freely diffusible tracer. Evidence shows that this assumption is not valid in the brain at high blood flow rates, at which movement of water into and out of the microvasculature becomes limited by diffusion across the blood-brain barrier. In this work, the arterial spin-labeling technique is used to show that fraction of arterial water that is dependent on blood flow rate remains in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
146
2

Year Published

1999
1999
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(151 citation statements)
references
References 28 publications
3
146
2
Order By: Relevance
“…This was corroborated by the fact that fitting of all ASL data (acquired at TIs from 0.3 to three seconds) with a CBF Ն 100 ml/100 g/minute was only successful if additional variables: 1) extraction fraction (E), and 2) outflow (T out ) time were included. Although there is a wide range of published values for E and T out (16,17,27), and the uncertainty in these estimates is high, it should be noted that in our study E is comparatively low and T out is quite large. Establishing more accurate estimates of these parameters would be an interesting goal for future studies.…”
Section: Discussioncontrasting
confidence: 56%
“…This was corroborated by the fact that fitting of all ASL data (acquired at TIs from 0.3 to three seconds) with a CBF Ն 100 ml/100 g/minute was only successful if additional variables: 1) extraction fraction (E), and 2) outflow (T out ) time were included. Although there is a wide range of published values for E and T out (16,17,27), and the uncertainty in these estimates is high, it should be noted that in our study E is comparatively low and T out is quite large. Establishing more accurate estimates of these parameters would be an interesting goal for future studies.…”
Section: Discussioncontrasting
confidence: 56%
“…(An additional sink may be the loss of inverted protons via flow-through to the muscular venules and venous collection vessels.) Previous theoretical treatments (1,12,13,17,22,28) have found that the product of flow and the effective T 1 (T 1eff ) is proportional to the difference in equilibrium magnetization between the label condition (inversion plane in the neck) and the control condition (inversion plane above the head):…”
Section: Theorymentioning
confidence: 99%
“…[1] and [13] express essentially the same relationship, to wit: with instantaneous equilibration of microvascular protons and tissue protons, the population of inverted protons in the tissue is proportional to the product of flow and T 1sat .…”
Section: Arterial Spin Tagging Viewed From the Capillarymentioning
confidence: 99%
See 2 more Smart Citations